Branchial Cyst in the Parapharyngeal Space: A Case Report - Iyad Said Hamadi; Lubna Lutfi; Asma Anan Mohammed; Zahr Alkhadem (Dubai Medical Journal)
Branchial cleft cysts are congenital anomalies that most commonly arise from a failure of fusion of the second branchial arch during embryonic life. They usually present as a swelling in the lateral side of the neck, below the mandible. In this article, we present a case of a 28-year-old female patient with a right branchial cyst measuring 7 × 6 × 5 cm, who presented with an asymptomatic, rapidly growing mass in the right anterior triangle of the neck that abutted the right external carotid artery, leading to stenosis of the vessel that is preceded by dilatation above the site of compression. She underwent excision of the cystic mass with preservation of the facial nerve and presented no active complaints on follow-up a few weeks postoperatively.